3(x+5)=2(x-6)

Simple and best practice solution for 3(x+5)=2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+5)=2(x-6) equation:


Simplifying
3(x + 5) = 2(x + -6)

Reorder the terms:
3(5 + x) = 2(x + -6)
(5 * 3 + x * 3) = 2(x + -6)
(15 + 3x) = 2(x + -6)

Reorder the terms:
15 + 3x = 2(-6 + x)
15 + 3x = (-6 * 2 + x * 2)
15 + 3x = (-12 + 2x)

Solving
15 + 3x = -12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
15 + 3x + -2x = -12 + 2x + -2x

Combine like terms: 3x + -2x = 1x
15 + 1x = -12 + 2x + -2x

Combine like terms: 2x + -2x = 0
15 + 1x = -12 + 0
15 + 1x = -12

Add '-15' to each side of the equation.
15 + -15 + 1x = -12 + -15

Combine like terms: 15 + -15 = 0
0 + 1x = -12 + -15
1x = -12 + -15

Combine like terms: -12 + -15 = -27
1x = -27

Divide each side by '1'.
x = -27

Simplifying
x = -27

See similar equations:

| 250/5-x=35 | | x-0.22x=93.60 | | 6g+9=-15-2g | | 4-3/w+1=5/w+2 | | 3x-10=110 | | P-6=-19 | | 1-0.5k=1 | | 6+8k-2= | | 6x+1+5x-3=86 | | 60*12-x=605 | | x+0.06x=23.54 | | 6(-4/3)^4+16(-4/3)^3 | | 4(2x-5)=5x+14 | | 12+(4n)=24 | | 7x-5+2x=x+15 | | 11/8= | | 8a+12a-2= | | y=11-6*2 | | x-48+137=742 | | M/-3=17 | | y=11-6*0 | | 1n+2(n)=21 | | 6s+3s=139.50 | | a=8w | | 182-7x=20x+23 | | 3=10/3x-12 | | 15=4-m | | 4q+15=6q-1 | | -1/2w-8/3=-7/5 | | 14+7X40/8-7 | | x-453=339 | | 12/7= |

Equations solver categories